Evaluation of blood component transfusion in sick neonates- a retrospective study in a rural tertiary new-born care unit of Eastern India - Khuntdar, Bidyut Kumar; Naik, Surjit; Patra, Kajal Kumar; Sau, Manabendra; Madhwani, Kishore P. (International Journal of Contemporary Pediatrics, 2022)
Background: In recent past, blood transfusion in neonates has developed a lot improving the outcome particularly in premature and low birth weight babies. However, there are no globally followed standardised guidelines for neonatal blood transfusion. The present study conducted with the objective to evaluate the frequency, indications, complications and appropriateness of various blood components transfusion in sick newborn care unit (SNCU) of a resource poor setting. Methods: This retrospective, hospital based, single centre observational study is done in a tertiary care SNCU of a teaching hospital of eastern India. All SNCU admitted neonates who received blood/ blood component transfusion from October 2018 to September 2019 were evaluated for blood component usage and their indications and followed up throughout hospital stay. The data were statistically analysed using Microsoft Excel™ software. Results: In this study 219 neonates received a total of 359 bags of blood component transfusion. Out of these packed red blood cell (PRBC), fresh frozen plasma (FFP), random donor platelet and whole blood were 233 (64.90%), 97 (27.01%), 10 (2.78%) and 19 (5.29%) respectively. The major indications for transfusion were anaemia of prematurity (35.37%), sepsis (26.18%) and bleeding disorder (16.71%). The common transfusion-related complications observed in our study were cardiac abnormality (22.35%), electrolyte disturbance (6.40%) and hypoglycaemia (19.17%). Conclusions: Anaemia of prematurity was the foremost indication of transfusion. Multiple transfusions were associated with prematurity and low birth weight.